Ludobójstwo – czyli zbrodnia, której nie ma - Kłos, Jan (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
While this paper refers mainly to the genocide in Volhynia, it is in fact an ethical and philosophical reflection on the question of crime as such. The historical examples of genocide (not only in Ukraine, or not even in Europe) are designed to show a broader context of motives that lead to criminal behaviour. Some actions are not the most important either. The author deems it more interesting to depict the overall complicated process of justifying the guilt: external (the political systems) and internal (showing the agent’s psyche). The process of rationalization that is at work here destroys any efforts to heal the relationship between the agent and his victim, for it thwarts conscience and inhibits the path to know the truth.